The anatomy of the root apex: A review and clinical considerations in endodontics - Osama S Alothmani; Nicholas P Chandler; Lara T Friedlander (Wolters Kluwer Medknow Publications, 2013)
Studies on the anatomy of the root apex are an area of interest to the endodontist; they have reported that the position of the apical constriction, apical foramen and the cemento-dentinal junction varies across the tooth types. These anatomical apical landmarks are considered extension limits for root canal instrumentation and filling. Achieving an optimum working length is thought essential for successful root canal treatment, so adopting any of these landmarks is associated with certain risks and benefits. The variability in the position of the apical constriction and apical foramen, for example, complicates their clinical detection, while the cemento-dentinal junction is a histological landmark that cannot be detected clinically. The radiographic apex does not always coincide with the anatomic apex of the tooth. The pre-operative status of the pulp must be considered while obtaining the working length. Most prognostic studies agree that extending the root filling to within 2-3 mm of the radiographic apex is associated with favorable treatment outcomes.